FINANCIAL WELL-BEING IN THE DIGITAL ERA : THE IMPACT OF DIGITAL KNOWLEDGE, FINANCIAL SKILLS AND FINTECH ADOPTION - Candy Candy; Vivin Mayviana; Dewi Khornida Marheni (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study looks at how digital knowledge, financial knowledge, and financial skills affect financial well-being. It also considers how using FinTech tools can influence this relationship. The research involved a survey with 400 respondents in Indonesia, and the data was analyzed using a method called Partial Least Squares-Structural Equation Modeling (PLS-SEM) to understand both direct and indirect effects. The findings show that digital knowledge, financial knowledge, and financial skills all have a positive effect on financial well-being, and using FinTech can make these effects even stronger. The mediation analysis shows that using FinTech helps make the connection between these skills and financial well-being stronger by making it easier to access and use financial services. This study adds to existing research by combining digital literacy, financial knowledge, and technology use into one model, giving important insights into how financial well-being is affected during digital changes, especially in poorer countries. The findings imply that policymakers, educators, and FinTech developers should promote financial and digital literacy programs while designing accessible and inclusive financial technologies to foster better financial outcomes for society.